Hepatotoxicity Due To Mushroom Poisoning: A Case Report - Baniasad, N; Oghabian, Z; Mehrpour, O (International Journal of Medical Toxicology and Forensic Medicine, 2014)
Background: Although the majority of mushroom ingestions are benign, some result in significant toxicity and death. Of greatest concern is the hepatotoxic amatoxin-containing mushroom, which may be fatal even small ingestions. Identification of amatoxin poisoning can prove to be difficult due to delay in onset of symptoms and difficulty with identification of mushrooms. Case Report: We present one case of mushroom ingestion in Kerman, province what according to clinical course and laboratory finding, we believe to be an amanita species, treated with multiple dose of activated charcoal, N-acetylcysteine, high-dose penicillin and liver Gol (silymarin). Conclusion: We present the successful treatment a patient who ingested hepato-toxicity induced mushrooms, further, this case is evidence of a mushroom variety responsible for toxicity never previously implicated in the southeastern Iran. <!--[if gte mso 9]> <![endif]-->